IMLEMENTASI FUNGSI MANAJEMEN KEPALA SEKOLAH TERHADAP PENINGKATAN KINERJA TENAGA PENDIDIKAN DAN KEPENDIDIKAN DI SD NEGERI 2 SEPANG JAYA KECAMATAN KEDATON KOTA BANDAR LAMPUNG - Umi Atiyah; Erjati abas; Etika Pujianti (UNISAN JURNAL, 2022)
Many State Elementary Schools are in the public spotlight regarding the quality of human resources, especially at SDN 2 SDN 2 Sepang Jaya, Labuhan Ratu Bandar Lampung District, 2021/2022 Academic Year, this is because in addition to being very large in number, the quality of human resource management has so far have not been able to align with other general education. It is necessary to implement a strategy, one of which is the continuous implementation of Planning, Organizing, Actuating, Human Resources. The focus of this research is Human Resource Management which is applied at SDN 2 SDN 2 Sepang Jaya, Labuhan Ratu Bandar Lampung District, 2021/2022 Academic Year, in this case includes: Planning for recruitment of personal approaches and selections that are not relevant to educational background. Aspects of the comparison, among others, comparisons of management of Human Resources Recruitment, Organizing Placements, Mobilizing human resources, and management The most important subjects in this study are the principal, teachers, school committees of the school, which have many similarities and differences in several aspects. Therefore, it is mandatory and is expected to become a treasure and input for the SDN 2 SDN 2 Sepang Jaya School, Labuhan Ratu Bandar Lampung District, for the 2021/2022 Academic Year. Keywords: principal management, performance of educators